2020
DOI: 10.1002/slct.202001988
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed DFT Study on Electronic Structures and Nonlinear Optical Properties of Doped C30

Abstract: We present a systematic study on structural, electronic, optical properties of C30 fullerene and its six doped counterparts, C10X10Y10 (where, X=B, Al and Y=N, P, As) based on density functional theory calculation. All the fullerenes are energetically stable with cohesive energy per atom ranging from −5 to −8 eV. Chemical reactivity parameters are significantly enhanced due to doping. Further, nonlinear optics reveal that dopants bring remarkable change in polarizability and first hyperpolarizability of C30 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Figure 3 depicts the effect of doping and interaction with CBZ of the and the percentage variation of the gap, , which measures the percentage variation of of the C 59 X after the CBZ adsorption on the fullerene cage (Table S5 present the numerical values of , , and . The change of the is an important parameter, since the energy gap is directly correlated with electrical conductivity (σ), σ ∝ exp(− E g /2k B T) 73 (T is the temperature, and k B represents Boltzmann constant) so that if the of the doped-fullerene is strongly affected by the presence of CBZ an electronic signal enables identification of the drug.
Figure 3 (Top panel) HOMO–LUMO gap energy (E g ) of C 59 X in the complex configuration (C 59 X + CBZ) in vacuum and water (PCM) and (lowest panel) percentual change of E g (ΔE g ) with respect to its value prior to the CBZ adsorption.
…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 depicts the effect of doping and interaction with CBZ of the and the percentage variation of the gap, , which measures the percentage variation of of the C 59 X after the CBZ adsorption on the fullerene cage (Table S5 present the numerical values of , , and . The change of the is an important parameter, since the energy gap is directly correlated with electrical conductivity (σ), σ ∝ exp(− E g /2k B T) 73 (T is the temperature, and k B represents Boltzmann constant) so that if the of the doped-fullerene is strongly affected by the presence of CBZ an electronic signal enables identification of the drug.
Figure 3 (Top panel) HOMO–LUMO gap energy (E g ) of C 59 X in the complex configuration (C 59 X + CBZ) in vacuum and water (PCM) and (lowest panel) percentual change of E g (ΔE g ) with respect to its value prior to the CBZ adsorption.
…”
Section: Resultsmentioning
confidence: 99%
“…Paul [5] 1). Paul et al [5] reported that the μ of C30 fullerene cage was calculated at 0.12 Debye by B3LYP functional with 6-311 + G (d, p) basis set.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to this property, it can have the ability to attract extra electrons and form a bound mono or poly-anion. Besides, it is nanostructures that have applications in arti cial photosynthesis and photovoltaic devices [5]. Despite all the theoretical and experimental studies, there are still many de ciencies in the characterization of fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we have investigated in uence of solvent on optical properties of nitrogen doped carbon molecules. We have calculated N doped carbon molecules with water and DMF as solvent 32,34,[46][47][48] . The data are listing in table 2.…”
Section: Halogen Doping and Halogen-nitrogen Co-doping Moleculesmentioning
confidence: 99%
“…Lu et al reported a novel kind of N and F co-doped CDs with D-π-A conjugated N-CDs-F, which have very bright deep-red emission and can be used for e cient in vivo NIR imaging 27 . To get a better insight about the underlying mechanism and stability of these CDs, chemical reactivity descriptors have been analyzed [28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%